Поливная посуда Крыма XV в. (местное производство до турецкого периода). Часть ІІ. Хронология - Тесленко, И. Б. (Давнина. Харківський історико-археологічний щорічник, 2016)
SummaryI. Teslenko. The Crimean Glazed Pottery of the 15th cent. (Local Production Before Turkish Invasion). Part II. ChronologyThe questions of detailed chronology of the local manufactured Glazed ceramics from Crimean 15th century archeological monuments are considered in article. For creation of a chronological scale of these artifacts the materials from well dating archeological complexes of different types are involved. The motives of ornaments, techniques of a decor, color scale and the manner of figures elements making have the chronological values for Glazed ceramics of the investigated period. The results of analysis once have allowed to create the detailed chronology of the local manufactured decorated ceramics and to allocate chronological indicators among them. These indicators allow dating archeological complexes within the limits of half, quarters and fewer centuries.Key words: Crimea, glazed ceramics, archaeological context, chronology, the chronological indicator.